1985
DOI: 10.1523/jneurosci.05-07-01851.1985
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and immunocytological localization of molluscan small cardioactive peptides in the nervous system of Aplysia californica

Abstract: High pressure liquid chromatography (HPLC) followed by bioassay on isolated snail hearts were used to locate two related peptides, termed small cardioactive peptides A and B (SCPA and SCPB) in each of the central ganglia of Aplysia. The peptides are most concentrated in the buccal ganglia, the ganglia involved in the control of feeding movements. Immunocytology with antisera raised to conjugated SCPB stained three groups of neurons in the buccal ganglia. One group consisted of relatively small neurons that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
90
0
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 0 publications
8
90
0
1
Order By: Relevance
“…Consistent with this complexity, previous work has shown that the feeding circuit is extensively modulated by neuromodulators, including neuropeptides that have been discovered in Aplysia (41,42,48,49,66,67,69). This study constitutes the first example of a DAACP acting as a neuromodulator in the Aplysia feeding circuit.…”
Section: Approaches For Identifying Daacps In Biological Tissuesupporting
confidence: 74%
“…Consistent with this complexity, previous work has shown that the feeding circuit is extensively modulated by neuromodulators, including neuropeptides that have been discovered in Aplysia (41,42,48,49,66,67,69). This study constitutes the first example of a DAACP acting as a neuromodulator in the Aplysia feeding circuit.…”
Section: Approaches For Identifying Daacps In Biological Tissuesupporting
confidence: 74%
“…One class of peptides that have been commonly found to coexist with other transmitters in Aplysia neurons are the small cardioactive peptides (SCPs) (6)(7)(8). The SCPs are represented by two peptides, SCPA and SCPB, which are 11 and 9 amino acids in length, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…These peptides have similar sequences, are derived from a common precursor polypeptide (9)(10)(11), and have been shown to satisfy many of the criteria required of neurotransmitters (12). They are present in, and synthesized by, individual neurons (6)(7)(8) and are contained in membrane-bound dense-core vesicles in central neurons and in varicosities in the central nervous system, muscle, and gut (13,14). Immunoreactive fibers and varicosities are present at both central and peripheral sites where the SCPs have been shown to potently modulate the efficacy of synaptic transmission (12,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Buccal ganglia were incubated with 0.5 mCi of [35S]methionine (1 Ci = 37 GBq; Amersham) for 24 hr at 18°C in 1 ml of 50% artificial sea water (ASW)/50% sterile (0.2-,um filtered) hemolymph/100 ,l of antibiotics (penicillin and streptomycin each at 50 units per ml)/colchicine (2.5 ,ul of 1 M colchicine dissolved in Me2SO). Colchicine was added to inhibit axonal transport, which raised intrasomatic peptide levels and reduced, or eliminated, labeled peptides that might be present in fibers and terminals near the somata of dissected neurons (12). After 24 hr, ganglia were rinsed and incubated in 50% sterilized hemolymph containing antibiotics and colchicine as described: 50% L15 culture medium (Flow Laboratories) plus salts for 4-6 hr.…”
mentioning
confidence: 99%